RESPON MASYARAKAT TERHADAP PELESTARIAN SEMPADAN SUNGAI DARI AKTIVITAS ANTROPOGENIK DAN PENGELOLAAN BERKELANJUTAN DI SEPANJANG ALIRAN SUNGAI SAWANG KECAMATAN SAWANG: Community Response To Anthropogenic Activities Along The Sawang River Watershed - Amar, Aidil; Maisura; Fahmi, Reza; Syifa (Journal of Sustainable Agribusiness, 2025)
This study aims to analyze the community response to anthropogenic activities, especially C-type mining, which occurs along the Krueng Sawang Watershed (DAS), North Aceh Regency. The study uses a quantitative descriptive approach with data collection through questionnaires, observation, and documentation. The results of the study indicate that C-type mining activities cause damage to river ecosystems such as abrasion, shallowing, and decreased water quality. The community shows sufficient ecological awareness, but has not been accompanied by active participation in environmental conservation. The majority of respondents are aware of the impact of these activities on agriculture, disaster risk, and infrastructure, but involvement in preventive actions is still low. Therefore, government intervention is needed through regulation, environmental education, and community involvement in sustainable watershed management.